Rhodnius stali: new vector infected by Trypanosoma rangeli (Kinetoplastida, Trypanosomatidae) - Gabriela Vieira de Souza Castro (Revista da Sociedade Brasileira de Medicina Tropical)
Abstract INTRODUCTION Rhodnius stali infection by Trypanosoma rangeli is reported in this study for the first time. METHODS The triatomines were collected from the campus of the Federal University of Acre in Rio Branco, Acre, Brazil. The identification of T. rangeli was confirmed by multiplex polymerase chain reaction. RESULTS The examinations of two specimens revealed R. stali infection by the epimastigote forms of T. rangeli. CONCLUSIONS The encounter of R. stali infected by T. rangeli generates an alert for the state of Acre, since the simultaneous presence with Trypanosoma cruzi can make the differential diagnosis of Chagas disease difficult.